Le tombeau de Charles Baudelaire sculpté par Stéphane Mallarmé - Wojtynek-Musik, Krystyna (Romanica Silesiana)
A detailed analysis of the sonnet Le tombeau de Charles Baudelaire reveals an intertextual game with Baudelaire, his old-time master of poetry, that Mallarmé undertook in order to highlight his own creative autonomy. At first, he exploits Baudelaire’s favourite poetic strategies, such as the wealth of sensual effects, an inner movement of images, hierarchic syntactic patterns, the principle of antithesis in the composition of the text, and the message conveyed allegorically. At the same time, however, Mallarmé introduces his own techniques into his master’s stylistic repertoire, e.g. a scarcity of sensual effects, a contemplative construction of images, parallel and elliptical syntax, the principle of complementary associations, and symbolism. His view of death is also different, although both poets consider it a sacred ritual of passage. Key words: Baudelaire’s poetry, Mallarmé’s poetry, intertextuality, poetic strategies, motif of death.